Effect of High-k Oxide on Double Gate Transistor Embedded in RF Colpitts Oscillator - M. Bella; S. Latreche; C. Gontrand (Журнал нано- та електронної фізики)
The Linear Time Variant (LTV) model of phase noise is considered. It is based on the Impulse Sensitivity Function (ISF) which describes carefully the sensitivity of an oscillator to a parasite impulse current injection in different nodes of the circuit. The obtained results pointed out that the ISF function is sinusoidal and its period is nearly the same of the oscillator output signal for different dielectric oxide. It also states that the phase noise of a Colpitts oscillator is not affected by the use of the high-k materials. Finally this method, if extended, is a good tool to investigate a perturbation response on such circuits.